Perancangan Sistem Informasi Pengolahan Data Jemaat Berbasis Website: (Studi Kasus: Gereja Kristen Sumba Jemaat Lambanapu) - Darmawan Juari K. Romu; Arini Aha Pekuwali; Desy Asnath Sitaniapessy (Neptunus: Jurnal Ilmu Komputer Dan Teknologi Informasi, 2025)
The design of a data processing information system is currently in great demand. By designing a data processing information system, the community, especially the congregation and administrators at the Sumba Christian Church (GKS) Lambanapu, can be facilitated in the process of data processing and providing information quickly, precisely and accurately, so that efficiency and effectiveness of church work are achieved. In this study, the author uses various writing methods including data collection techniques, waterfall methods, and system development methods. Creating an information system in church data processing that should be able to improve service performance and be able to provide fast and accurate information. So that it can help the process of church member data collection and can be a means of conveying information to church members. Creating a web-based system used for congregation or congregation data at the Sumba Christian Church (GKS) Lambanapu which contains applications for member registration, baptism registration, marriage blessing registration, sidi registration, registration for borrowing worship facilities and infrastructure, as well as downloading member documents, and news about church activities.